An Online Educational Hackathon to Foster Professional Skills and Intense Collaboration on Software Engineering Students - Steglich, Caio; Marczak, Sabrina; Guerra, Luiz; Trindade, Cássio; Dutra, Alessandra; Bacelo, Ana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
The global pandemic of COVID19 demanded that professors rethink teaching strategies considering the use of online environments due to the social isolation stipulated to reduce the rate of contagion of the disease. A challenge for software engineering professors is to develop fundamental professional skills in students who are in the process of learning using these virtual environments. The purpose of this study is to identify how an online educational hackathon can support students of a Software Engineering program to develop professional skills. We also seek to understand how intense collaboration takes place between student teams, considering the digital context for the production of a technological solution. We conducted a Case Study on an educational hackathon that took place in the online context, collecting data through questionnaires, interviews, and observations. As some results, the skills that students most considered that this hackathon helped them to develop were communication, initiative, and creativity/innovation, among others. Also, the strategies of collaboration adopted by the students during this competition, considering the remote context. Therefore, the main contribution is the identification of how the realization of this event supported students to develop professional skills and to practice collaboration skills with each other.